2011
DOI: 10.1590/s1983-14472011000200026
|View full text |Cite
|
Sign up to set email alerts
|

Tendências da produção do conhecimento de enfermagem no controle de infecção em oncologia

Abstract: Os clientes com câncer apresentam complicações significativas de morbi-mortalidade relacionadas à infecção. Esta revisão integrativa tem como objetivo analisar a produção científica da enfermagem acerca do controle de infecções nos clientes com câncer. A busca dos 37 artigos incluídos foi por meio eletrônico em bases de dados, no período de 2002 a 2009. Os dados foram analisados na perspectiva da Metodologia de Categorização Epistemológica para a Pesquisa na Enfermagem. Os resultados indicam que a produção é i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It has been shown that these mobile health interventions have small to moderate effects on physical activity and sedentary behavior. 23 It was found that, even with the good results using mobile health applications, not all studies were able to stimulate behavior change in the participants and, perhaps, the failure of educational software to promote change in be in not using behavioral change techniques. For this reason, it is suggested that there is insufficient behavior change strategies in applications to manipulate these variables, or that the use of the application was not intensive enough to evoke changes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that these mobile health interventions have small to moderate effects on physical activity and sedentary behavior. 23 It was found that, even with the good results using mobile health applications, not all studies were able to stimulate behavior change in the participants and, perhaps, the failure of educational software to promote change in be in not using behavioral change techniques. For this reason, it is suggested that there is insufficient behavior change strategies in applications to manipulate these variables, or that the use of the application was not intensive enough to evoke changes.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies in annotations on phlogistic signs by the nursing team may worsen the hospital infection issues described as predominant in oncological patients. In fact, the nursing team should select priority strategies in the prevention of these diseases (Sanhudo, Moreira, & Carvalho, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the same results, neutropenia can be identified, which is one of the side effects of chemotherapy that indicates infection risk (24)(25) and orients nurses to start the clinical pathway for febrile neutropenia or perform screening. Studies have demonstrated the effective reduction of infection risks when nursing care pathways are employed in oncology practice (24) .…”
Section: Literature Findings Show That Nurses Play An Importantmentioning
confidence: 99%
“…Studies have demonstrated the effective reduction of infection risks when nursing care pathways are employed in oncology practice (24) . At the same time as neutropenia is identified, patient and family education actions are undertaken that emphasize preliminary knowledge on signs and symptoms and orientation about infection risks.…”
Section: Literature Findings Show That Nurses Play An Importantmentioning
confidence: 99%